Effects of gene flow from IMI resistant sunflower crop to wild Helianthus annuus populations - Presotto, Alejandro Daniel (2012)
Wild sunflower, H. annuus ssp. annuus, is an invasive species widely distributed in several regions of the world, including central Argentina where it shares a large area with domesticated sunflower. The discovery of imidazolinone resistance in a wild sunflower population allowed the development of Clearfield® technology in cultivated sunflower. This technology was rapidly adopted in Argentina but the trait could possibly be transferred to the naturalized wild populations through natural hybridization. The aim of this study was to evaluate the transfer of IMI resistance to wild sunflower populations and its effect on wild plants? fitness. Plants of five wild populations and their progenies of crosses with an IMI-resistant hybrid were evaluated through a dormancy, herbicide resistance, and SSR markers study. Relative fitness was compared in the five populations, F1s and backcrosses with wild and crop parental plants. Hybridization with an IMI-resistant hybrid did not alter seed dormancy. F1 individuals were more resistant to imazapyr than their wild ancestors but less tolerant than the commercial variety. SSR markers confirmed the transfer of resistance and identified resistant plants within the wild populations. Fitness was reduced in the first generation after crossing but was recovered in the following generations. Thus, to ensure durability and efficiency of Clearfield® technology, management practices like crop rotation and herbicide usage with different modes of action should be considered.